(untitled) (Journal of Informatics Education and Research, 2025)
This study aims to examine how Arab students at higher education institutions in Israel perceive their previous school principals’ principalship styles, oral communication skills, and conflict resolution approaches, as related to the students’ academic performance and identity. It was important to conduct this research because there is currently limited understanding about the ways school leadership could impact students, particularly minority students, development over an extended period of time, in complicated sociopolitical circumstances. In many ways, this research makes vital contributions to reveal the contextualized influence of school principals’ relational and motivational dimensions to nurture students’ resilience, motivation, and academic trajectories. Using a qualitative methodology, data were collected through semi-structured interviews of a diverse population of 40 Arab students, from varied academic levels. The study’s findings reveal the positive influence of a future-focused principalship style, empathic communication skills, and inclusive conflict resolution practices on the students’ motivation, sense of belonging, and success. The study recommends including principals’ leadership training that incorporates empathy, communication, and culturally efficacious student-centered leadership strategies.